Enabling social participation for older people: The content of reablement by age, gender, and level of functioning in occupational therapists' interventions. (18th August 2022) - Pettersson, Cecilia; Zingmark, Magnus; Haak, Maria
Abstract: Background: Social participation and the ability to build and maintain social relationships is emphasized as important for older people's health and well-being. Aim: To explore if social participation is addressed and whether age, gender and level of functioning are associated with the composition of occupational therapy interventions within the context of reablement. Method: In this cross-sectional study, invitations to participate were sent to 60 municipalities in Sweden. 318 occupational therapists participated and described the character of initiated interventions made during 3 weeks through web-based surveys. Result: 1392 cases were reported in the age span of 19–103 years, 61.7% were women. A higher proportion of persons having no home care and minor functional dependency got interventions with a focus on social participation to a higher extent than persons with major functional dependency. Occupational therapists' interventions vary as related to functional limitation, age, and gender. Conclusion: The results indicate that the severity of functional limitation impacts the focus of the intervention whereas age and gender do not. There is a need for social participation to be more clearly addressed within the context of reablement. Significance: To develop a person-centred intervention, one needs to consider aspects of age, gender, and functions.